(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Wave modeling for reconstruction and hind casting is essential for a wide range of engineering and oceanographic applications. However, this process becomes significantly more complex within island archipelagos com pared to the open sea, as it involves intricate physical phenomena that are challenging to capture accurately. In this study, a coupling between REEF3D::FNPF and SWAN, a well-known large-scale phase-averaged numerical model, is implemented to model wave patterns in the Azores archipelago. Time-domain SWAN simulations are con ducted using a nested grid approach to refine results within the region of interest. Wind and open-boundary wave data are sourced from the ERA5 reanalysis dataset, available through the Climate Data Store (CDS), while bathymet ric data for the study area is obtained from EMODNet. Results from the coarse-resolution SWAN non-stationary simulations are used as input for both REEF3D::FNPF, and localized stationary SWAN simulations. The simulated wave fields are then compared against statistical wave data acquired from Spotter platforms operated by blueOASIS, deployed in the Faial-Pico channel, and from the CLIMAAT project wave buoys, managed by Universidade dos A¸ cores, positioned 1 NM SWawayfromthecoastofPontaDelgada, S˜ ao Miguel. This approach demonstrates the ability to assess localized spatiotemporal scales of wave dynamics and complex physical phenomena typically occurring in island archipelagos, such as diffraction, reflection, and refraction. Moreover, this work serves as the foundation for developing a Digital Twin (DT) solution that integrates real-time in-situ data from sensors with versatile numerical representations of metocean environmental conditions.